Magic Color Batik sebagai Media Edukatif untuk Meningkatkan Kreativitas Motorik Halus dan Kebanggaan Budaya Anak Usia Dini - Chahyani, Isna Nur; Muslam, Muslam; Afrih Lia, Naila Fikrina (UNIB Press, 2026)
The purpose of this study is to explain how Magic Color Batik works to enhance creativity, fine motor skills, and culture in early childhood at RA IT Nurul Islam. Innovative, entertaining, and developmentally appropriate culture-based learning media are essential, which is the background for this study. This study was conducted using a qualitative approach and designed as a case study. The research subjects were teachers and 16 children from group A aged 4-5 years, and they were involved in the research through observation, interviews, and documentation in October-November. The results showed that children's creativity could be enhanced by using Magic Color Batik. This was demonstrated by their courage to express their ideas, diversity of color choices, and development of simpler motifs. In addition, children's fine motor skills developed, especially in terms of their ability to control tools, control hand pressure, and regulate hand-eye coordination when Batik making. Furthermore, the children showed enthusiasm and pride in Batik as part of their local culture. Teachers believe that Magic Color Batik is easy to use, safe, and can create a fun and beneficial learning environment. Studies show that Magic Color Batik is a relevant, efficient, inexpensive, and useful learning medium for use in early childhood education activities, especially for teaching art and strengthening cultural identity from an early age.